2014
DOI: 10.3762/bjoc.10.298
|View full text |Cite
|
Sign up to set email alerts
|

Thermal and oxidative stability of the Ocimum basilicum L. essential oil/β-cyclodextrin supramolecular system

Abstract: Summary Ocimum basilicum L. essential oil and its β-cyclodextrin (β-CD) complex have been investigated with respect to their stability against the degradative action of air/oxygen and temperature. This supramolecular system was obtained by a crystallization method in order to achieve the equilibrium of complexed–uncomplexed volatile compounds in an ethanol/water solution at 50 °C. Both the raw essential oil and its β-CD complex have been subjected to thermal and oxidative degradation conditions in order to eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…Siddique et al [ 27 ] suggested that the chemical compositions of essential oil depend largely on its colour. Moreover, the alteration of the essential oil colour as a result of their compositions is suggested to be due to thermal degradation, oxidation, isomerisation, dehydrogenation and polymerisation [ 17 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Siddique et al [ 27 ] suggested that the chemical compositions of essential oil depend largely on its colour. Moreover, the alteration of the essential oil colour as a result of their compositions is suggested to be due to thermal degradation, oxidation, isomerisation, dehydrogenation and polymerisation [ 17 , 27 , 28 , 29 ].…”
Section: Resultsmentioning
confidence: 99%
“…Analysis of the thermal stability of laurel, oregano, and rosemary VOCs showed that all terpenes indicated a likelihood of thermo-degradation and monocarbonyl compounds, and hexanal, 2-hepaenal, and 2,4decadienal appeared as a result of autoxidation [95]. Hădărugă et al also reported that terpenes, including sesquiterpenes, had a greater susceptibility to degradation than the corresponding alcohols, and as such epoxidated sesquiterpenes and monoterpenes were found to be abundant after high temperature treatment [96]. The degradation of VOCs can result in a reduction in their bioactivities, for example, their antioxidant capacity.…”
Section: Deactivation By Heat and Airmentioning
confidence: 99%
“…CDs might enhance the solubility of EOs and their components thus higher concentrations could be used, produce easy measurable dosage forms, facilitate their dispersion and protect them from interactions with other excipients . CDs could also retain and allow a controlled release for EOs, offer them thermal, oxidative, light and chemical stability and increase their oral bioavailability . To the best of our knowledge no previous study attempted to investigate the inclusion complexes of Captisol® (sulfobutylether‐β‐cyclodextrin, SBE‐β‐CD) and Captisol‐G® (sulfobutylether‐γ‐cyclodextrin, SBE‐γ‐CD) with EOs and their components while, compared to native CDs, these CDs exhibit greater water solubility and a more desirable safety profile …”
Section: Introductionmentioning
confidence: 99%
“…with other excipients. 10 CDs could also retain and allow a controlled release for EOs, 11,12 offer them thermal, oxidative, light and chemical stability [13][14][15][16][17] and increase their oral bioavailability. 18 To the best of our knowledge no previous study attempted to investigate the inclusion complexes of Captisol® (sulfobutylether-β-cyclodextrin, SBE-β-CD) and Captisol-G® (sulfobutylether-γ-cyclodextrin, SBE-γ-CD) with EOs and their components while, compared to native CDs, these CDs exhibit greater water solubility and a more desirable safety profile.…”
mentioning
confidence: 99%